2003
DOI: 10.1046/j.1365-2826.2003.00959.x
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Regulation of N‐Methyl‐d‐Aspartic Acid Receptor Subunit mRNA Expression in Adult Brain

Abstract: Thyroid hormone is an essential modulator of brain development, but little is known about its actions in the adult brain. Hypothyroidism is associated with gene expression changes in both central and peripheral nervous tissue. Functional consequences of adult-onset hypothyroidism include an inability to produce long-term potentiation in rat hippocampus and impaired learning and memory in both rats and man. Long-term potentiation is a form of learning that is dependent on functional N-methyl-d-aspartic acid (NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
3
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 42 publications
2
52
3
1
Order By: Relevance
“…The hippocampus is a highly sensitive neural structure that is known to be involved in learning and memory and it is a highly vulnerable brain area to the action of thyroid hormones (46), this may be related to the presence of the high content of thyroid receptors (27). Hippocampal synaptic plasticity is widely assumed to represent a mechanism, by which memory is encoded, consolidated and stored (21).…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampus is a highly sensitive neural structure that is known to be involved in learning and memory and it is a highly vulnerable brain area to the action of thyroid hormones (46), this may be related to the presence of the high content of thyroid receptors (27). Hippocampal synaptic plasticity is widely assumed to represent a mechanism, by which memory is encoded, consolidated and stored (21).…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormone treatment failed to normalize these two neurophysiological abnormalities observed in hypothyroid animals [42], as expected from our finding that thyroxine treatment depressed electrical responses within the DG. Although neither the expression of NMDARs nor DG histology was examined in the present study, we believe that one possible mechanism by which the findings of impaired LTP and spatial learning may be explained is through the change in expression of different NMDAR subunits, including NR1 mRNA or NR2B mRNA [38,52,53]. Given that PTP was also affected by thyroxine application, it seems worth considering that some of the effects of thyroxine may involve presynaptic as well as postsynaptic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…It is surprising that even T3-treated rats showed impaired performance on a spatial task when compared to their matched controls [36], a finding that may be explained by the nongenomic effects of thyroid hormones. Several groups have shown that thyroid hormones inhibit L -[ 3 H]glutamate binding [37], regulate N-methyl- D -aspartate (NMDA) receptor subunit expression in the hippocampus [38], and decrease NMDA-evoked currents in rat hippocampal cultures [39]. It is also known that glutamate and glutamatergic receptors are involved in synaptic plasticity in hippocampal neurons [22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that hypothyroidism is associated with changes of gene expression in both central and peripheral nervous system (Kobayashi et al, 2005). Inability to produce LTP in rat hippocampus and impaired learning and memory in both rats and man are among functional consequences of adult-onset hypothyroidism (Lee et al, 2003). The other researchers believe that hypothyroidism affects behavioral conditions (Burmeister et al, 2001;Smith et al, 2002;Whybrow and Bauer, 2005) and is accompanied by emotional symptoms, including lethargy and dysphoria (Capet et al, 2000;Dugbartey, 1998;Haggerty et al, 1990).…”
Section: Introductionmentioning
confidence: 99%